2002
DOI: 10.1105/tpc.003046
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins Are Required for Seed Development and Pollen Tube Growth in Arabidopsis

Abstract: Gibberellins (GAs) are tetracyclic diterpenoids that are essential endogenous regulators of plant growth and development. GA levels within the plant are regulated by a homeostatic mechanism that includes changes in the expression of a family of GA-inactivating enzymes known as GA 2-oxidases. Ectopic expression of a pea GA 2-oxidase2 cDNA caused seed abortion in Arabidopsis, extending and confirming previous observations obtained with GA-deficient mutants of pea, suggesting that GAs have an essential role in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(181 citation statements)
references
References 47 publications
9
168
1
3
Order By: Relevance
“…Indeed, there was no evidence for discrimination against triple mutant seeds in the progeny of this cross. This finding was unexpected in the light of results using GA-deficient mutant and transgenic plants that indicated a requirement for GA in pollen development, pollen tube growth, and seed development (Swain et al, 1997;Singh et al, 2002;Cheng et al, 2004). It is therefore possible that these processes use GA signaling pathways that are independent of the GID1 receptors.…”
Section: The Gid1 Triple Mutant Displays Severe Growth Defectsmentioning
confidence: 60%
See 1 more Smart Citation
“…Indeed, there was no evidence for discrimination against triple mutant seeds in the progeny of this cross. This finding was unexpected in the light of results using GA-deficient mutant and transgenic plants that indicated a requirement for GA in pollen development, pollen tube growth, and seed development (Swain et al, 1997;Singh et al, 2002;Cheng et al, 2004). It is therefore possible that these processes use GA signaling pathways that are independent of the GID1 receptors.…”
Section: The Gid1 Triple Mutant Displays Severe Growth Defectsmentioning
confidence: 60%
“…In Arabidopsis, they promote floral initiation and the development of floral organs, seeds, and siliques (Wilson et al, 1992;Singh et al, 2002;Cheng et al, 2004). To assess the involvement of the Arabidopsis GID1 genes in these developmental processes, we have characterized reproductive development in all combinations of mutants.…”
Section: Reproductive Growth and Developmentmentioning
confidence: 99%
“…While previous work has shown that GAs are required for plant embryogenesis (Singh et al, 2002), this study shows the necessity for plants to down-regulate GA biosynthesis in embryos. The fine-tuning of GA biosynthesis regulation is likely to involve cross-talk between other plant hormone pathways such as ABA, ethylene, or auxin that also play a role in embryogenesis.…”
Section: Regulation Of Atga3ox2 Expression By Fus3mentioning
confidence: 75%
“…Two genes, At4g33790 and At3g51280, encoding MS2-and MS5-like proteins, respectively, are identified as RGA down-regulated genes. In addition to pollen development, GA is also required for normal pollen tube growth in the sexual reproduction of plants (Singh et al, 2002;Swain et al, 2004). Cellulose, hemicellulose, and pectin are three major carbohydrates making up the primary cell wall in most plant cells, while the wall of the pollen tube tip is only composed of a single layer of pectin.…”
Section: Rga Predominantly Regulates Stamen and Pollen Developmentmentioning
confidence: 99%